Experimental Simulation-Based Performance Evaluation of an SMS-Based Emergency Geolocation Notification System. (30th August 2017) - Osebor, Isibor; Misra, Sanjay; Omoregbe, Nicholas; Adewumi, Adewole; Fernandez-Sanz, Luis
Abstract : In an emergency, a prompt response can save the lives of victims. This statement generates an imperative issue in emergency medical services (EMS). Designing a system that brings simplicity in locating emergency scenes is a step towards improving response time. This paper therefore implemented and evaluated the performance of an SMS-based emergency geolocation notification system with emphasis on its SMS delivery time and the system's geolocation and dispatch time. Using the RAS metrics recommended by IEEE for evaluation, the designed system was found to be efficient and effective as its reliability stood within 62.7% to 70.0% while its availability stood at 99% with a downtime of 3.65 days/year.